Impact of COVID-19 in food supply chain: Disruptions and recovery strategy - Barman, Abhijit (Current Research in Behavioral Sciences, 2021)
BACKGROUND: The COVID virus epidemic has produced another era on the planet while we sort out the outcomes in various parts of our everyday life. The food industry and food supply chain do not incorporate an exception. Considering a food supply chain, the business activities and supply of various food products have been suspended due to restriction of demand, closing the food production facilities, financial restrictions. SCOPE AND APPROACH: According to the spreadability of the pandemic, every nation must understand the seriousness of the circumstance. This work aims to discuss the effect of COVID-19 on socioeconomic implications and the impact of lockdown on the food supply chain and agri-business. The paper also summarizes the suggestions needed to control and deduce the impact of COVID-19. For now, the chance of transmission through the food area is viewed as immaterial, and following Covid in workspaces isn't considered as a need by public authorities. However, the unfriendly impacts on the climate, food frameworks and individuals along the food store network are obvious. KEY FINDINGS AND CONCLUSION: A food supply chain facilities should concentrate on facilities like maintenance of employees' safety and health, change of conditions in working. To prevent the increment of food prices, the protectionist policy should avoid. We have also suggested a PDS system to overcome food supply chain disruption. In conclusion, the supply chain should respond and overcome the challenging situation in the food supply chain.